Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin. (2nd November 2021) - Tahir, Halima; Muhammad, Nadeem; Intisar, Azeem; Din, Muhammad Imran; Qaisar, Uzma; Qadir, Muhammad Abdul; Ain, Noor Ul; Ahmad, Zeeshan; Aziz, Pakeeza; Shahzad, Muhammad Khurram; Hussain, Irshad
Abstract: In this study, the essential oil composition and antibacterial activity of the resin of Canarium strictum Roxb. was investigated. The oil was extracted by microwave-assisted extraction and analyzed through gas chromatography-mass spectrometry by means of which 35 compounds were successfully identified. A substantial yield of essential oil (1.10%) was obtained from the resin. The most abundant ingredients were (R)-(+)-limonene (59.03%) and 1 R-(+)-α-pinene (24.06%). Antibacterial activity evaluation was performed against five bacterial strains four of which were multidrug-resistant. The oil was found to be active against all the strains. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values in mg/mL were calculated where MIC values were: methicillin-resistant Staphylococcus aureus (>0.66), Pseudomonas aeruginosa (1.33), Klebsiella pneumoniae (5.3), resistant Escherichia coli (>0.66) and non-resistant Escherichia coli (5.3).